Hubungan Orangtua dengan Guru dalam Upaya Meningkatkan Hasil Belajar Anak anak di Desa Sei Siur - Pranoto, Muhammad Solihin; Rahma, Winda (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
The cooperation between parents and teachers has a good impact in improving student learning outcomes. This is because parents are able to see the development of their children / students through teachers and or vice versa. A teacher is able to get information about his children / students through parents. This study aims to determine the relationship between parents and teachers in trying to improve the learning outcomes of children / students in Sei Siur Village, Pangkalan Susu District by conducting interviews with parents and people who work as teachers in the village. The result of this study is that the relationship between parents and teachers can be done by doing good communication to ask about the development of children / students and the difficulties of children / students in learning. And each parent has its own efforts in improving the learning outcomes of their children / students such as repeating lessons, registering children / students to take lessons, and arranging children's / students' learning and play schedules and so on. This study found significant results that the relationship between parents and teachers in improving children's / students' learning outcomes can be done by doing good communication to ask about the development of children / students and the difficulties of children / students in each learning.Â Â